Incremental and transformative adaptation preferences of rice farmers against increasing soil salinity - Evidence from choice experiments in north central Vietnam. (May 2021) - Dam, Thi Huyen Trang; Tur-Cardona, Juan; Speelman, Stijn; Amjath-Babu, T.S.; Sam, Anu Susan; Zander, Peter
Abstract: Context: Increasing salinity levels demand adaptative and transformative changes in farming systems in regions affected by saltwater intrusion intensified by global climate change. The study area, a narrow delta affected by salinity intrusion due to rising sea levels as well as by diminishing rainfall during the dry season in north-central coastal region of Vietnam represents this global challenge. Apart from the level of salinity, farmer characteristics, legal framework and the expected returns to investment on the available choices shape the future trajectories of these farming systems. Nevertheless, relatively less research efforts are focused on understanding these choices and the trade-offs. Objective: The study focus on identifying and determining the acceptability of adopting stress tolerant rice varieties, changes in cropping sequences, or a transformative shift to aquaculture conditional to the degree of saltwater intrusion as well as gaining insight into required policy changes to facilitate the adaptation and transformation in rice farming deltas. Methods: The current study reports a novel choice experiment (CE) approach to analyse the roles of risk attitude, expected returns, production costs, effort levels and legal restrictions on the preferences for adaptation alternatives and their interactions with salinity levels using random parameter models. Results and conclusions: The results reveal the role of perceived risks and labour efforts in adaptative choices and highlight the need for risk offset mechanisms as well as labour-saving interventions. The simulations using the estimated random parameter models predict farmers affected by salinity below the critical threshold of 4 dS/m of electrical conductivity (EC) will have a 34.4% adoption rate for traditional rice and a 43.6% rate for salinity-tolerant rice varieties, which will drop by 2 to 3 percentage points when the current legal restrictions on conversion to aquaculture are waived. In the case of farmers facing higher salinity levels, aquaculture would likely become the dominant option, with 40% of the cohort of farmers adopting aquaculture (17.2% adopting shrimp and 22.4% adopting polyculture), followed by saline-tolerant rice (36% to 38%). Significance: The results reveal the need for increased investment in rice breeding for salinity tolerance, market development for alternative crops, introduction of risk offset mechanisms and a planned shift to transformative alternatives such as aquaculture. The findings of this study call for a balanced effort for adaptative and transformative options for rice farmers, infrastructural options preventing salinity intrusion and enhanced global mitigation efforts to reduce the possible rise in sea levels and limit salinity intrusion. Graphical abstract: Unlabelled Image Highlights: Increasing salinity fosters adaptive and transformative responses among paddy farmers. Adoption of ST rice varieties can reach 43% in presence of land use restrictions. Transformation to aquaculture can reach 40% if land use restrictions are waived. Innovation to reduce risks is vital for driving adaptive responses against salinity. Salinity intrusion require balanced soft and hard adaptive strategies with mitigation.